(untitled) (Eurasian Journal of Philology Science and Education, 2022)
The names of the lands and rivers hide the most diverse layers of cultural and spiritual life, the tragic events of the centuries-old political and social life of this ethnic group. Despite the fact that in linguistics, various facts of Kazakh toponymy has been published, such problems of toponyms as the system of myths of the local ethnic groups, have not become the object of a specific, comprehensive study yet. The purpose of research is to describe some toponyms mythological nature in Kazakh language, combined with the common Turkic sacred concept of “sacred, holy” in the meaning of “rich”, “female deity”. The semantic and etymological analysis of the composition of the name Katonkaragai, Bayanaul, the identification of mythological basis of concepts of “goddess”, “female goddess” in worldview of the Turkic-speaking and Kazakh peoples, determines the relevance of the article. As a result of the analysis, the followings were achieved:-the cognitive level of the Kazakh people comes from ancient Turkic mythological worldviews; -the commonality of the content and ideas of myths common to the entire Turkic world, i.e. their sound correspondences in the nature of the mythical text of the ancient Turkic Umai-female God, Mother of God; -our attempt to justify in a new way the reflection of the sacred concept of “female God” in the toponyms Bayanaul, Katonkaragai on the basis of the research done and previously ignored sources determines the scientific and practical significance of the work. The methods of descriptive, historical-comparative analysis were used in study. The mythological understandings of Kazakhstan and other Turkic-speaking peoples were comparatively analyzed on the basis of etymology, described in popular scientific literature and in mythotexts of ancient Turkic dictionaries, compared with real linguistic data and reasons for the origin. Key words: Mythonym, mythotoponym, Umai, Bayanaul, Katonkaragai, Katun, Muztau